Fulani herdsmen/farmers conflict and the challenges of food security in the middle belt region of Nigeria - Inyang Etim Bassey; Eke Nta Effiong; E Offiong Ekwutosi (International Journal of Humanities and Innovation (IJHI), 2021)
The agriculture sector, the backbone of an economy, provides the basic ingredients to mankind and raw material for industrialization. It plays a strategic role in the process of economic development and growth. Leading industrialized countries of today were once predominantly agricultural economies and still dominate in agriculture. The agriculturalsector contributes a major proportion of the national income and caters to a large workforce segment. However, one of the biggest security challenges in Nigeria lately is the expanding clashes between farmers and herders. Today, the conflict has spread over several regions in Nigeria and the Middle-Belt-Region specifically. It is against this foundation that this research is carried out to inspect how conflicts between farmers and herders influence food production, food accessibility, food stability, and food usage in the Middle Belt. The study is based on selected secondary sources and findings from the field research conducted in the Middle Belt region such as Benue, Taraba, Adamawa, Bauchi, Nasarawa, etc. The qualitative research techniques involved in-depth interviews with local people and direct observation. This study observes that the food insecurity in this region is driven by the constant clash between the farmers and herdsmen, which have inflicted fear of going to cultivate their farmland in the lives of these rural farmers, consequently leading to shortages in food production in the region.